2013
DOI: 10.1161/circinterventions.112.000079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residual Chronic Total Occlusion of Right Coronary Artery on the Long-term Outcome in Patients Treated for Unprotected Left Main Disease

Abstract: W ith continual improvements in stent technology and adjunctive pharmacotherapy, we have supportive evidence regarding percutaneous coronary intervention (PCI) and drug-eluting stent (DES) implantation in selected unprotected left main (ULM) lesions involving ostium/body or distal bifurcation with low-to-moderate SYNTAX scores. [1][2][3][4][5][6][7][8] Conversely, in patients with SYNTAX score >32, coronary artery bypass grafting (CABG) is recommended. 9 The presence of chronic total occlusion of the right cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This review will focus on the development of new techniques for CTO PCI with an emphasis on procedurally relevant histopathology and the differing methodologies that have emerged from sites in Japan and the United States of America. A discussion of the prognostic importance of CTOs and the rationale for revascularisation is beyond the scope of this review and has been published elsewhere [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…This review will focus on the development of new techniques for CTO PCI with an emphasis on procedurally relevant histopathology and the differing methodologies that have emerged from sites in Japan and the United States of America. A discussion of the prognostic importance of CTOs and the rationale for revascularisation is beyond the scope of this review and has been published elsewhere [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RCA CTO was recognized as an independent predictor of 3-year cardiac mortality (HR 2.15 [1.02-4.05]; P = 0.043). In line with these results, Takagi et al [7] concluded that in patients undergoing ULM PCI, cardiac death was higher in patients with residual RCA CTO as compared to those without residual RCA CTO (HR 2.163 [1.018-4.597]; P = 0.045) at 1466 days follow-up. Besides, they showed that recanalization of RCA CTO significantly improves long-term survival (P = 0.010).…”
mentioning
confidence: 74%
“…Many trials have investigated the relationship between the risk of mortality and CTO in various populations. 1 2 3 4 5 6 The HORIZONS-AMI trial reported that the presence of CTO was an independent predictor of both increased early (within 30 days, HR: 2.88, 95% CI: 1.41–5.88, p =0.004) and late mortality (from 30 days to 3 years, HR: 1.98, 95% CI: 1.19–3.29, p =0.009) in STEMI patient. 2 The PL-ACS study, reported CTO was an independent predictor of 1-year mortality (HR: 1.42, 95% CI: 1.01–2.00, p =0.047) in patients with non-STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the presence of CTO is associated with a higher mortality rate in patients with acute myocardial infarction, multi-vessel disease (MVD), or left main disease. 1 2 3 4 5 6 The presence of CTO has also been shown to be associated with a reduced left ventricular ejection fraction (LVEF; <40%) and further deterioration of LVEF in ST-segment elevation myocardial infarction (STEMI) patients. 5 In the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry, 61% of CTO patients were treated with medical therapy (MT), while only one third (39%) were treated with early coronary revascularization by percutaneous coronary intervention (PCI; 24%) or coronary artery bypass graft surgery (CABG; 15%).…”
Section: Introductionmentioning
confidence: 99%